Rechargeable vs. Nonrechargeable Internal Pulse Generators in the Management of Dystonia. Issue 3 (30th January 2013) - Gillies, Martin J.; Joint, Carole; Forrow, Beth; Fletcher, Clare; Green, Alexander L.; Aziz, Tipu Z.
<x xml:space="preserve">Abstract</x> Objective To test if deep brain stimulation (DBS) treatment of dystonia was similar in patients before and after implantation of rechargeable internal pulse generators (IPGs). Materials and Methods The Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS) severity and disability scores were compared in patients before DBS insertion, 24 months after DBS insertion with a nonrechargeable IPG, and after implantation of a rechargeable IPG. Results No significant differences were observed between dystonia control in patients before and after implantation of a rechargeable IPG. Conclusions Rechargeable IPGs should be the IPGs of choice for dystonic patients receiving DBS as IPGs offer similar treatment efficacy to nonrechargeable IPGs with advantages in terms of costs and reductions in reimplantation frequency.